Recurrent longitudinally extensive transversal myelitis in a patient with Sjögren’s syndrome - Šekarić, Jelena; Živanović, Željko; Lučić - Prokin, Aleksandra; Kokai - Zekić, Timea; Petrović, Kosta; Turkalj, Ivan; Jovin, Zita; Gvozdenović, Slobodan (Vojnosanitetski pregled, 2013)
Introduction. Longitudinally extensive transverse myelitis (LETM) is a transversal myelitis that extends through three or more vertebral segments in length. Case report. A 52-year-old woman was hospitalized due to pain in the lumbar region, difficulty in walking, hypoesthesia of the anogenital area and urinary retention. In the past medical history, two years earlier, the patient had been diagnosed with transversal myelitis confirmed by MRI of the cervical spine and six months earlier, the patient was diagnosed with primary Sjögren’s syndrome (SS). During the current hospitalization MRI of the spinal cord revealed extensive inflammatory lesions of almost the whole spinal cord. Lumbar puncture (LP) revealed mild pleocytosis and slightly increased protein level. Isoelectric focusing of cerebrospinal fluid (CSF) and serum proteins was normal. Visual evoked potentials were normal. Serological testing excluded acute viral infections. Corticosteroid therapy was applied with good therapeutic response. Control MRI revealed regression of pathological changes in the spinal cord. Conclusion. A wide range of disorders can cause LETM, but usually the first line diagnosis is neuromyelitis optica (NMO). Based on the detection of NMO immunoglobulin G in the serum of affected patients, a variety of allied disorders were grouped under the name of NMO spectrum disorders, including recurrent myelitis associated with LETM and myelitis associated with autoimmune disorders such as SS. There have been only a few cases reported in the literature with recurrent LETM associated with non-organ specific autoimmune disorder.
Keywords: myelitis; transverse; sjorgen’s syndrome; neuromyelitis optica; diagnosis; drug therapy; treatment outcome